Internal Fixation of Type I Capitellum Fracture with Headless Screws: A Case Report - Charlie Sanjaya; I Ketut Gede Arta Bujangga (Journal Orthopaedi and Traumatology Surabaya)
Background: Capitellum fractures are relatively rare. Distal humeral fractures that include capitellum and trochlea constitute approximately 6% of all distal humeral fractures and 1% of all elbow fractures. Despite the rarity of these injuries, an increasing number of clinical series have emerged, enhancing our understanding of these fractures.